Entre a fé e o orgulho : as articulações das narrativas jornalísticas dos portais Veja e Carta Capital na construção de polarizações entre evangélicos e LGBTs - Jênifer Rosa de Oliveira (2023)
The research entitled "Between faith and pride : the articulations of the journalistic narratives of the Veja and Carta Capital portals in the construction of polarizations between Evangelicals and LGBTs" investigates how journalistic narratives interrelate Evangelicals and LGBT groups; and also the implications from these articulations to the representations of what it is to be an evangelical in Brazil. The object of analysis are textualities found on the Veja and Carta Capital websites, published over the past decade (2010-2019), which somehow address themes that are disclosed as being of interest to both groups. The process of selecting and organizing the texts was based on Bardin's (2004) content analysis method, which made it possible to structure the stages and methods of observing the analyzed material. Subsequently, the information extracted from these stages were interpreted in the light of narrative theory - threefold mimesis - by Paul Ricoeur (2010), and discussions on journalism and construction of reality (ALSINA, 2009; SILVA, 2011; 2013), based on concepts such as framing analysis (ANTUNES, 2009; TUCHMAN, 1993; ENTMAN, 1993) and journalism as a social actor in the construction of conflicts (VENTURINI, 2009; AMOSSY, 2017; CARVALHO, 2012; 2019). The hypothesis, which remained proven during the course of the research, was that the journalistic narrative acts in the construction of the antagonisms found between evangelicals and LGBTs by always welcoming the same voices and characters to speak on behalf of both groups. These narrative strategies, more than promoting debate, promote the crystallization of conservative stereotypes about what it means to be an evangelical in Brazil. They also contribute to the silencing of the LGBT cause, by putting themselves at the service of controversial discourse, which, in turn, works to maintain the status quo of hegemonic social structures, and not for the emancipation of the individuals.